2017
DOI: 10.1111/jfpp.13329
|View full text |Cite
|
Sign up to set email alerts
|

Determination of antibiotic susceptibility and decarboxylase activity of coagulase-negativeStaphylococcusandMacrococcus caseolyticusstrains isolated from fermented Turkish sausage (sucuk)

Abstract: The aim of this research was to detect antibiotic susceptibility patterns and amino acid decarboxylase activity of 61 presumptive coagulase‐negative Staphylococcus (CNS) strains from the Turkish dry fermented sausage (sucuk). The presumptive CNS strains were identified at species levels as 21 S. saprophyticus, 16 S. epidermidis, 10 Macrococcus caseolyticus, 4 S. xylosus, 3 S. sciuri, 2 S. hominis, 2 S. warneri, 1 S. cohnii, 1 S. pasteuri, and 1 S. vitulinus by 16S rDNA sequence analysis. S. saprophyticus and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…But Organji et al [ 48 ] observed in their study on milk in Egypt that S. saprophyticus was the most dominant coagulase-negative strain. This difference in proportion can be explained by the fact that our samples were not fermented enough because S. saprophyticus plays a role in the fermentation process [ 49 ]. In this respect, probably no health risks are associated with all Staphylococci detected in fermented dairy products samples.…”
Section: Discussionmentioning
confidence: 99%
“…But Organji et al [ 48 ] observed in their study on milk in Egypt that S. saprophyticus was the most dominant coagulase-negative strain. This difference in proportion can be explained by the fact that our samples were not fermented enough because S. saprophyticus plays a role in the fermentation process [ 49 ]. In this respect, probably no health risks are associated with all Staphylococci detected in fermented dairy products samples.…”
Section: Discussionmentioning
confidence: 99%
“…Also Mammaliicoccus sciuri itself, has been the subject of many taxonomical reclassifications in the past (3,6). Its current genus name refers to the ecological niche from which these bacteria are typically isolated, being a wide variety of farm and wild mammals, as well as products derived thereof (7)(8)(9)(10)(11). Although mostly exhibiting a commensal lifestyle on its animal hosts, M. sciuri has been occasionally associated as an opportunistic pathogen associated with mastitis, dermatitis, and exudative epidermitis (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%